Strategi Akuisisi Konten Institusional Repository Perpustakaan UIN Sunan Kalijaga - Isrowiyanti, Isrowiyanti (Pustakaloka, 2017)
Institusional repository (IR) is an information resource getting spread in some university libraries in Indonesia in the last ten years, including UIN Sunan Kalijaga library. IR as to be an important information resource alternative to the user on acessing information are produced by UIN Sunan Kalijaga academicians. The study aim to know some aspects on IR content aquisition was generated by UIN Sunan Kalijaga library, and how the strategy on encreasing the academicians angagement in IR content acquisition. The study find that the self upload policy of the academician works, and the rectorâs decision that all of academician must submit their works to the library as the important things on increasing the academician engagement in the IR content acquisition.